Fast food as drivers for overweight and obesity among urban school children at Jakarta, Indonesia - Febriani, Dian; Sudarti, Trini (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
The study aimed to analyse dominant factors associated with overweight and obesity among students in Perguruan Cikini Elementary School in Central Jakarta. A cross-sectional study was conducted between March-May 2017 with 145 participants from 3rd, 4th, and 5th grades. Data obtained were measurement of body weight and height, physical activity questionnaire for children, food frequency questionnaire and 24-hour food recall. Prevalence of overweight and obesity among students in Perguruan Cikini Elementary School in Central Jakarta was 41.4%. Based on logistic regression, fast food consumption was a dominant factor associated with overweight and obesity among students in Perguruan Cikini Elementary School in Central Jakarta. Students who consumed fast food >3 times/week were 2.42 times more likely to be overweight and obese compared to students who consumed fast food ≤3 times/week.